A SEMIOTIC ANALYSIS OF FASHION DOMINATION THROUGH SIGNS IN MUSIC VIDEOS - Khairunnisa, Erika (2013)
This paper entitled "A Semiotic Analysis of Fashion Domination through Signs in Music Videos" aims to investigate domination issues in the form of fashion by examining denotative, connotative, and mythical meanings of selected scenes in three music videos. The three music videos are Ailee's "I Will Show You", Taylor Swift's "You Belong with Me", and Super Junior M's "Super Girl". The orders of signification were used as the semiotic tools to analyze the data. The results show that a change of appearance emerges in the music videos as a form of domination to maintain the dominant ideology. Penelitian ini yang berjudul "A Semiotic Analysis of Fashion Domination through Signs in Music Videos" bertujuan untuk menginvestigasi isu-isu dominasi dalam bentuk fesyen dengan menelaah makna-makna denotasi, konotasi, dan mitos dari adegan-adegan pilihan dalam tiga video musik. Tiga video musik itu adalah Ailee "I Will Show You", Taylor Swift "You Belong with Me", dan Super Junior M "Super Girl". Orders of signification digunakan sebagai alat semiotik untuk menganalisa data tersebut. Hasilnya menunjukkan bahwa perubahan penampilan di dalam video-video musik itu muncul sebagai sebuah bentuk dominasi untuk mempertahankan ideologi dominan.